Moisture-curable resin composition

CN122953271APending Publication Date: 2026-10-20THREE BOND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580020519.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-18
Filing Date
2025-02-04
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]为了解决上述问题,需要不使用聚硅氧烷和锡催化剂的粘接剂、密封剂,但是存在对塑料的粘接性低的问题

Benefits of technology

[0003]为了解决上述问题,需要不使用聚硅氧烷和锡催化剂的粘接剂、密封剂,但是存在对塑料的粘接性低的问题。另外,若提高对工程塑料的粘接性,则存在由于材质的刚性的不同而导致对金属的粘接性降低的问题。进而,作为粘接剂、密封剂,难以具有适当的稳定的粘接性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a moisture-curing resin composition that exhibits high adhesion to metals and plastics without the use of polysiloxanes and tin catalysts, and further, provides stable adhesive properties as both an adhesive and a sealant. This invention relates to a moisture-curing resin composition comprising: (A) a polyoxyethylene polymer having a hydrolyzable silyl group and a (meth)acrylic polymer having a hydrolyzable silyl group; (B) a silane coupling agent having one or more epoxy groups per molecule; and (C) a titanium catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a moisture-curing resin composition that exhibits excellent adhesion to metals and plastics and has stable bonding properties. Background Technology

[0002] Against the backdrop of automotive lightweighting, the use of resin raw materials is increasing in automotive electrical components that constitute the next generation of EVs and HVs. Previously, FIPGs (Filmed In-Situ Gaskets) were mostly used as adhesives and sealants in automobiles. For example, as in the technology disclosed in Japanese Patent Application Publication No. 2006-143985, the main raw material of conventional FIPGs was polysiloxane. However, FIPGs containing polysiloxanes may cause contact failures due to low-molecular-weight siloxanes, making them difficult to apply to automotive electrical components. Furthermore, conventional FIPGs used tin catalysts as curing catalysts, which have been restricted from regulatory perspectives. Therefore, when used as adhesives and sealants, stable adhesive performance is required. Stable adhesive performance can be judged by the failure state when an external force is applied after bonding. Specifically, in the case of interfacial failure, where the failure occurs at the interface between the adherend and the adhesive or sealant, the deviation in bond strength increases due to the deviation in the interface state, which is not preferred. However, in the case of cohesive failure, where the failure occurs within the adhesive or sealant, the bond performance is stable. Summary of the Invention

[0003] To address these issues, adhesives and sealants that do not use polysiloxanes and tin catalysts are needed; however, these suffer from low adhesion to plastics. Furthermore, improving adhesion to engineering plastics leads to reduced adhesion to metals due to differences in material rigidity. Consequently, as adhesives and sealants, it is difficult to achieve adequate and stable bonding performance.

[0004] In order to achieve the above-mentioned objectives, the inventors conducted in-depth research and as a result, discovered a moisture-curing resin composition that exhibits high adhesion to metals and plastics without the use of polysiloxanes and tin catalysts, and thus, as an adhesive and sealant, also possesses stable adhesive properties.

[0005] The main idea of ​​this invention will now be explained.

[0006] [1] A moisture-curing resin composition comprising the following components (A) to (C):

[0007] (A) Ingredients: Polyoxyethylene polymers with hydrolyzable silanes and (meth)acrylic polymers with hydrolyzable silanes;

[0008] (B) Composition: A silane coupling agent having one or more epoxy groups per molecule;

[0009] (C) Composition: Titanium catalyst.

[0010] [2] The moisture-curing resin composition according to [1] does not contain a silane coupling agent having one or more amino groups in one molecule.

[0011] [3] The moisture-curing resin composition according to [1] or [2] further comprises a plasticizer as component (D).

[0012] [4] According to the moisture-curing resin composition of [3], wherein the above-mentioned component (D) is a castor oil modified fatty acid ester.

[0013] [5] According to the moisture-curing resin composition of [3] or [4], wherein the amount of component (D) is 1 to 100 parts by mass relative to 100 parts by mass of component (A).

[0014] [6] The moisture-curing resin composition according to any one of [1] to [5] further comprises an inorganic filler as component (E).

[0015] [7] The moisture-curing resin composition according to [6], wherein the above-mentioned component (E) comprises heavy calcium carbonate powder and / or light calcium carbonate powder.

[0016] [8] The moisture-curing resin composition according to any one of [1] to [7] further comprises a silane compound having a reactive functional group other than alkoxysilyl in one molecule.

[0017] [9] The moisture-curing resin composition according to any one of [1] to [8] is used for bonding plastic components.

[0018]

[10] A cured product obtained by curing any one of the wet-curing resin compositions described in any one of [1] to [9]. Detailed Implementation

[0019] The following is a detailed description of the methods for implementing the present invention. The embodiments shown herein are illustrative examples to concretize the technical concept of the present invention and are not intended to limit the invention. Therefore, all other methods, uses, and techniques that can be implemented by those skilled in the art without departing from the spirit of the present invention are included within the scope and spirit of the present invention, and are included within the scope of the invention described in the technical solution and its equivalents. The embodiments described in this specification can be combined in any way to form other embodiments. It should be noted that in this specification, the range “X~Y” means “X or more and Y or less”, and “weight” and “mass”, “weight%” and “mass%”, and “parts by weight” and “parts by mass” are treated as synonyms. In this specification, “A and / or B” includes A or B, and forms of A and B. In this specification, unless otherwise specified, the operation and physical properties are measured under conditions of room temperature (20°C or higher and 25°C or lower) and relative humidity (RH) of 40% or higher and 50% or lower.

[0020] <Moisture-curing resin compositions>

[0021] One aspect of the present invention is a moisture-curing resin composition comprising: (A) a component: a polyoxyethylene polymer having a hydrolyzable silyl group and a (meth)acrylic acid polymer having a hydrolyzable silyl group; (B) a component: a silane coupling agent having one or more epoxy groups in one molecule; and (C) a titanium catalyst. The moisture-curing resin composition of this aspect exhibits excellent adhesive strength to metals and plastics and has stable adhesive properties. Therefore, the moisture-curing resin composition of this aspect is suitable for use as an adhesive and a sealant.

[0022] The components contained in the moisture-curing resin composition described herein will be described in turn below.

[0023] [(A) Ingredient]

[0024] The component (A) used in the moisture-curing resin composition described herein is a polyoxyethylene polymer having hydrolyzable silyl groups and a (meth)acrylic polymer having hydrolyzable silyl groups. That is, component (A) is a mixture of (a1) the polyoxyethylene polymer having hydrolyzable silyl groups and (a2) the (meth)acrylic polymer having hydrolyzable silyl groups. From a disposal point of view, component (A) is preferably liquid at 25°C. In component (A), the polyoxyethylene polymer having hydrolyzable silyl groups can be used alone or in combination of two or more. Similarly, in component (A), the (meth)acrylic polymer having hydrolyzable silyl groups can be used alone or in combination of two or more.

[0025] Polyoxyolefin polymers are polymers whose main chain contains an olefin backbone. Examples of olefins include polyethylene glycol, polypropylene glycol, polytrimethylene glycol, and polytetramethylene glycol. These polyoxyolefin polymers can be homopolymers or copolymers.

[0026] Hydrolyzable silyl groups refer to groups with 1 to 3 hydrolyzable groups bonded to silicon atoms. Examples of hydrolyzable groups include halogen atoms, alkoxy groups, acyloxy groups, ketoximate groups, amino groups, amide groups, aminooxy groups, and alkenyloxy groups. From the viewpoint of curability, alkoxy groups are preferred.

[0027] Examples of alkoxy groups include methoxy, ethoxy, propoxy, isopropoxy, butoxy, tert-butoxy, phenoxy, and benzyloxy. From the viewpoint of adhesive strength, methoxy and ethoxy are preferred, with methoxy being the most preferred. These alkoxy groups can be used alone or in combination of different types. As hydrolyzable silyl groups, trimethoxysilyl and triethoxysilyl are preferred.

[0028] As a method for manufacturing polyoxyethylene polymers with hydrolyzable silane groups, it is sufficient to introduce the hydrolyzable silane group onto the polyepoxide (oxyethylene backbone) as the main chain. For example, the polyoxyethylene polymer with hydrolyzable silane groups can be manufactured by known methods described in Japanese Patent Application Publication No. 63-012632 and Japanese Patent Application Publication No. 63-033425.

[0029] The backbone of (meth)acrylic acid polymers only needs to be derived from the structure of (meth)acrylic acid. Here, (meth)acrylic acid is a general term that includes acrylic acid and methacrylic acid, and (meth)acrylate is a general term that includes acrylate and methacrylate.

[0030] There are no particular limitations on the (meth)acrylic monomers used in the synthesis of (meth)acrylic polymers; various (meth)acrylic monomers can be used. (Meth)acrylic monomers are a general term for monomers containing an acryloyl group or a methacryloyl group. Examples of monomers in the (meth)acrylate class include (meth)acrylate, methyl methacrylate, ethyl methacrylate, methacrylates, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, n-heptyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, dodecyl methacrylate, phenyl methacrylate, toluene methacrylate, benzyl methacrylate, 2-methoxyethyl methacrylate, 3-methoxybutyl methacrylate, and 2-methoxyethyl methacrylate. Hydroxyethyl ester, 2-hydroxypropyl methacrylate, stearate methacrylate, glycidyl methacrylate, 2-aminoethyl methacrylate, γ-(methacryloyloxypropyl)trimethoxysilane, ethylene oxide adduct of methacrylate, trifluoromethyl methacrylate, 2-trifluoromethyl methacrylate, 2-perfluoroethyl methacrylate, 2-perfluoroethyl methacrylate, 2-perfluoroethyl-2-perfluorobutyl methacrylate, 2-perfluoroethyl methacrylate, perfluoromethyl methacrylate, diperfluoromethyl methacrylate, 2-perfluoromethyl-2-perfluoroethyl methacrylate, 2-perfluorohexyl methacrylate, 2-perfluorodecyl methacrylate, 2-perfluorohexadecyl methacrylate, etc., but not limited to these.

[0031] As monomers for manufacturing (meth)acrylic acid polymers, (meth)acrylic acid monomers can be appropriately selected, and (meth)acrylic acid monomers having hydrocarbon groups are preferred. (Meth)acrylic acid polymers can be obtained by various polymerization methods, and the methods are not particularly limited, but free radical polymerization is preferred from the perspective of monomer versatility and ease of reaction control. Among free radical polymerizations, controlled free radical polymerization is preferred, living free radical polymerization is more preferred, and atom transfer radical polymerization is particularly preferred. As a method for manufacturing (meth)acrylic acid polymers having hydrolyzable silyl groups, it is sufficient to introduce hydrolyzable silyl groups into the (meth)acrylic acid polymer as the main chain. For example, (meth)acrylic acid polymers having hydrolyzable silyl groups can be manufactured by methods known in publications such as Japanese Patent Application Publication No. 2000-154205.

[0032] In the moisture-curing resin composition described herein, the hydrolyzable silyl group in component (A) may be present in either the side chain or the end of component (A), but from a moisture-curing perspective, it is preferred to be present at the end or both ends of the main chain. More specifically, in polyoxyethylene polymers, the hydrolyzable silyl group may be present in either the side chain or the end of the polyoxyethylene polymer, but from a moisture-curing perspective, it is preferred to be present at the end or both ends of the main chain. In (meth)acrylic polymers, the hydrolyzable silyl group may be present in either the side chain or the end of the (meth)acrylic polymer, but from a moisture-curing perspective, it is preferred to be present in the side chain.

[0033] In component (A), there are preferably two or more hydrolyzable silane groups, more preferably three or more, and even more preferably four or more. More specifically, in polyoxyethylene polymers, there are preferably two hydrolyzable silane groups, and in (meth)acrylic polymers, there are preferably two or more hydrolyzable silane groups.

[0034] The viscosity of component (A) at 23°C is preferably 1 to 500 Pa·s, more preferably 10 to 300 Pa·s, further preferably 20 to 200 Pa·s, particularly preferably 30 to 180 Pa·s, and most preferably 50 to 150 Pa·s. If it is 1 Pa·s or more, the workability as a moisture-curing resin composition is good; if it is 500 Pa·s or less, the workability will not decrease even when mixed with components (B) and (C). The viscosity of component (A) is a value obtained by measuring using a BS type viscometer.

[0035] In component (A), the mass ratio of the polyoxyethylene polymer having hydrolyzable silyl groups to the (meth)acrylic polymer having hydrolyzable silyl groups is preferably 40:60 to 95:5, more preferably 45:65 to 90:10, and even more preferably 50:50 to 90:10. If the mass ratio of the polyoxyethylene polymer to the (meth)acrylic polymer is within the above range, superior adhesive strength can be achieved for both metals and plastics.

[0036] (A) The preferred components are a mixture of hydrolyzable silyl alkyl polyoxyethylene and a hydrolyzable silyl (meth)acrylic polymer; or a mixture of hydrolyzable silyl polyoxypropylene and a hydrolyzable silyl (meth)acrylic polymer.

[0037] Commercially available products that are part of ingredient (A) are not specifically limited to any particular type, but examples include MA440, MA447, MA451, MA903, MA903M, MA904, etc. (manufactured by KANEKA CORPORATION). They can be used alone or in combination of two or more.

[0038] In the moisture-curing resin composition described herein, the amount of component (A) relative to 100% by mass of the composition is preferably 10-95% by mass, more preferably 15-90% by mass, further preferably 18-85% by mass, particularly preferably 20-80% by mass, and most preferably 25-75% by mass. According to one embodiment, in the moisture-curing resin composition described herein, the amount of component (A) relative to 100% by mass of the composition is 20-70% by mass, 20-65% by mass, 20-60% by mass, 20-50% by mass, or 25-50% by mass. If the amount of component (A) is within the above range, superior adhesive strength can be achieved for both metals and plastics.

[0039] [(B) Component]

[0040] The component (B) used in the moisture-curing resin composition described herein is a silane coupling agent having one or more epoxy groups per molecule. Component (B) improves the bonding strength to metals and plastics, as well as the cohesive failure rate. Specific examples of component (B) include, but are not limited to, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, and 3-epoxypropoxypropyltriethoxysilane. They can be used alone or in combination of two or more. From the viewpoint of improving the bonding strength to metals and plastics and increasing the cohesive failure rate, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, and 3-epoxypropoxypropyltriethoxysilane are preferred.

[0041] The moisture-curing resin composition described herein preferably does not substantially contain a silane coupling agent (aminosilane coupling agent) having one or more amino groups per molecule. If the moisture-curing resin composition described herein contains an amino-containing silane coupling agent, the adhesion to metals and plastics decreases. Furthermore, due to the reaction with component (B), the bond strength and cohesive failure rate to metals and plastics decrease. "Substantially does not contain" here means that the amount incorporated is less than 0.1% by mass relative to 100% by mass of the total moisture-curing resin composition. Examples of silane coupling agents having one or more amino groups per molecule include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and hydrochloride salts of N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane. According to one embodiment, in the moisture-curing resin composition described herein, component (B) is a silane coupling agent having one or more epoxy groups per molecule and no amino group.

[0042] The amount of component (B) relative to 100 parts by weight of component (A) is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 18 parts by weight, further preferably 0.5 to 16 parts by weight, particularly preferably 1 to 15 parts by weight, and most preferably 3 to 10 parts by weight. If the amount of component (B) is within the above range, it is possible to improve the bonding strength to metals and plastics and the cohesive failure rate without any concern about reducing storage stability.

[0043] [(C) Component]

[0044] The component (C) that can be used in the moisture-curing resin composition described in this method is a titanium catalyst. In the moisture-curing resin composition described in this method, component (C) is the curing catalyst of component (A), and by combining it with components (A) and (B), it can improve the bond strength and cohesive failure rate to metals and plastics. Specific examples of component (C) include tetraisopropyl titanate, tetra-n-butyl titanate, tetrabutyl titanate dimer, tetraoctyl titanate, titanium acetylacetone, tetraacetylacetone titanium, ethyl acetoacetate titanium, titanium dodecylbenzenesulfonate compound, titanium phosphate complex, titanium octyl glycol, titanium ammonium lactate, titanium lactate, triethanolamine titanium, tetraisopropyl titanate, tetra-tert-butyl titanate, tetrastearate titanate, titanium acetylacetone, titanium octyl glycol compound, titanium isostearate, titanium lactate, titanium ammonium lactate, diethanolamine titanium, aminoethylaminoethanol titanium, etc., but are not limited to these. They can be used alone or in combination of two or more. From the perspective of improving the bonding strength and cohesive failure rate of metals and plastics, chelate-based titanium catalysts such as titanium tetraacetylacetone, titanium dodecylbenzenesulfonate, titanium phosphate ester complex, titanium octanediol, titanium ethyl acetoacetate, titanium acetylacetone, and titanium octanediol are preferred, titanium acetylacetone, titanium tetraacetylacetone, and titanium ethyl acetoacetate are more preferred, and diisopropyl bis(ethyl acetoacetate) titanate is the most preferred.

[0045] The amount of component (C) relative to 100 parts by weight of component (A) is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 18 parts by weight, further preferably 0.5 to 16 parts by weight, particularly preferably 1 to 15 parts by weight, and most preferably 3 to 10 parts by weight. If the amount of component (C) is within the above range, a cured product with excellent adhesion strength to metals and plastics and a high rate of cohesive failure can be obtained without concern about reduced storage stability.

[0046] [(D) component]

[0047] The moisture-curing resin composition described herein preferably further includes a plasticizer as component (D). Component (D) is broadly classified into phthalate-based plasticizers and non-phthalate-based plasticizers. From the perspective of low carcinogenicity and maintaining the effects of the present invention, non-phthalate-based plasticizers are preferred. There are no particular limitations on non-phthalate-based plasticizers; examples include (meth)acrylic acid polymer plasticizers obtained by polymerizing (meth)acrylic acid monomers; polyether polyol plasticizers such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyester plasticizers obtained from dibasic acids such as sebacic acid and adipic acid with diols such as ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol; processing oil plasticizers; alkyl sulfonates, tributyl acetylacetonate; castor oil-modified fatty acid esters, etc. These can be used alone or in combination of two or more. From the viewpoint of not reducing the bonding strength and cohesive failure rate to metals and plastics, castor oil modified fatty acid esters and / or alkyl sulfonate phenyl esters are preferred, and castor oil modified fatty acid esters are most preferred.

[0048] The amount of component (D) relative to 100 parts by mass of component (A) is preferably 1 to 100 parts by mass, more preferably 5 to 80 parts by mass, even more preferably 8 to 75 parts by mass, particularly preferably 10 to 70 parts by mass, and most preferably 20 to 60 parts by mass. By keeping the amount of component (D) within the above range, the cured product can be made soft without reducing the bond strength or cohesive failure rate.

[0049] [(E) component]

[0050] The moisture-curing resin composition described herein may further contain an inorganic filler as component (E). By including component (E) in the moisture-curing resin composition described herein, the resin strength can be improved. Examples of components (E) include talc powder, silica powder, clay powder, calcium carbonate powder, magnesium carbonate powder, calcium silicate powder, glass powder, alumina powder, zinc oxide powder, magnesium oxide powder, aluminum nitride powder, boron nitride powder, carbon powder, diamond powder, gold powder, silver powder, copper powder, nickel powder, etc., but are not limited to these. From the viewpoint of improving the resin strength without reducing the bond strength and cohesive failure rate, it is preferable to include calcium carbonate powder, preferably both heavy calcium carbonate powder (E-1) and light calcium carbonate powder (E-2), and most preferably both untreated heavy calcium carbonate powder (E-1) and light calcium carbonate powder (E-2) treated with fatty acids in the surface treatment.

[0051] From the viewpoint of improving resin strength without reducing bond strength and cohesive failure rate, the average particle size of component (E) is preferably 0.01 to 10 μm, more preferably 0.02 to 8 μm, further preferably 0.03 to 7 μm, particularly preferably 0.03 to 6 μm, and most preferably 0.03 to 5 μm. Here, when component (E) is heavy calcium carbonate powder (E-1), the average particle size of component (E-1) is preferably 0.01 to 10 μm, more preferably 0.02 to 8 μm, further preferably 0.05 to 7 μm, particularly preferably 0.1 to 6 μm, and most preferably 0.5 to 5 μm. When component (E) is light calcium carbonate powder (E-2), the average particle size of component (E-2) is preferably 0.01 to 10 μm, more preferably 0.01 to 5 μm, further preferably 0.02 to 3 μm, particularly preferably 0.02 to 2 μm, and most preferably 0.03 to 1 μm. By ensuring that the average particle size of components (E-1) and (E-2) is within the aforementioned range, the bond strength and cohesive failure rate can be further improved. The average particle size in this invention is the value of the particle size (D50) at which the cumulative volume ratio in the particle size distribution is 50%, determined by laser diffraction scattering.

[0052] From the viewpoint of compatibility with component (A), the BET specific surface area of ​​component (E) is preferably 1000 cm². 2 / g~50000cm 2 / g, more preferably 1500cm 2 / g~40000cm 2 / g, further preferably 2000cm 2 / g~30000cm 2 / g, with a particularly preferred value of 2500cm 2 / g~25000cm 2 / g, the optimal value is 3000cm 2 / g~20000cm 2 / g. When component (E) is heavy calcium carbonate powder (E-1), the BET specific surface area of ​​component (E-1) is preferably 3000 cm². 2 / g~50000cm 2 / g, more preferably 3500cm 2 / g~40000cm 2 / g, further preferably 5000cm 2 / g~30000cm 2 / g, with a particularly preferred value of 7500cm 2 / g~25000cm 2 / g, the optimal value is 8000cm 2 / g~20000cm 2 / g. When component (E) is light calcium carbonate powder (E-2), the BET specific surface area of ​​component (E-2) is preferably 1000 cm². 2 / g~30000cm 2 / g, more preferably 1200cm 2 / g~20000cm 2 / g, further preferably 1500cm 2 / g~15000cm 2 / g, preferably 2000cm 2 / g~10000cm 2 / g, the optimal value is 3000cm 2 / g~8000cm 2 / g. By ensuring that the BET specific surface areas of components (E-1) and (E-2) are within the above range, it is possible to further improve the bond strength and cohesive failure rate.

[0053] The amount of component (E) relative to 100 parts by mass of component (A) is preferably 10 to 300 parts by mass, more preferably 20 to 280 parts by mass, further preferably 50 to 250 parts by mass, particularly preferably 80 to 220 parts by mass, and most preferably 100 to 200 parts by mass. By keeping the amount of component (E) within the above range, the resin strength can be improved without reducing the bond strength and cohesive failure rate. When both components (E-1) and (E-2) are contained, the mass ratio of the amounts ((E-1):(E-2)) is preferably 10:90 to 70:30, more preferably 10:90 to 50:50, further preferably 15:85 to 50:50, particularly preferably 20:80 to 5:50, and most preferably 25:75 to 50:50. By keeping the mass ratio of components (E-1) and (E-2) within the above range, the bond strength and cohesive failure rate can be further improved.

[0054] [additive]

[0055] The moisture-curing resin composition described herein may further contain appropriate amounts of additives such as preservation stabilizers, antioxidants, colorants, and organic fillers (components (F) to (I)) without impairing its properties.

[0056] [(F)Component]

[0057] The moisture-curing resin composition described herein may include a preservation stabilizer as component (F). Examples of components (F) (preservation stabilizer) include silane compounds that do not have reactive functional groups other than alkoxysilyl groups. By including a silane compound that does not have reactive functional groups other than alkoxysilyl groups in the moisture-curing resin composition described herein, the residual reaction of component (A) is suppressed. In this specification, examples of reactive functional groups other than alkoxysilyl groups include vinyl, epoxy, (meth)acryloyl, amino, isocyanurate, urea, mercapto, isocyanate, anhydride, and carboxyl groups, but are not limited to these. Specific examples of silane compounds that do not have reactive functional groups other than alkoxysilyl groups include alkylsilane compounds such as methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, n-propyltrimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltriethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, and decyltriethoxysilane. These can be used alone or in combination of two or more. From the viewpoint of improving the storage stability of the moisture-curing resin composition described herein, it is preferable to include methyltrimethoxysilane and / or diphenyldimethoxysilane, and more preferably, methyltrimethoxysilane and diphenyldimethoxysilane. The amount of component (F) (preservation stabilizer) relative to 100 parts by mass of component (A) is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and most preferably 1.0 to 10 parts by mass. By setting the amount of component (F) within the above range, preservation stability is improved without any risk of reducing curability. When both methyltrimethoxysilane and diphenyldimethoxysilane are included as component (F), the mass ratio of methyltrimethoxysilane to diphenyldimethoxysilane (methyltrimethoxysilane: diphenyldimethoxysilane) is preferably 99:1 to 50:50, more preferably 95:5 to 50:50, further preferably 90:10 to 50:50, particularly preferably 85:15 to 55:45, and most preferably 85:15 to 60:40. By keeping the mass ratio of methyltrimethoxysilane to diphenyldimethoxysilane within the above range, storage stability can be improved without reducing adhesive strength or cohesive failure rate.

[0058] [(G) component]

[0059] In the moisture-curing resin composition described herein, an antioxidant may be included as component (G). By including an antioxidant as component (G), a cured product with excellent heat resistance can be obtained. Examples of antioxidants include quinone compounds such as β-naphthoquinone, 2-methoxy-1,4-naphthoquinone, methylhydroquinone, hydroquinone, hydroquinone monomethyl ether, mono-tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, p-benzoquinone, 2,5-diphenyl-p-benzoquinone, and 2,5-di-tert-butyl-p-benzoquinone.Phenothiazine, 2,2-methylene-bis(4-methyl-6-tert-butylphenol), catechol, tert-butylcatechol, 2-butyl-4-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 4,4'-butylenebis(6-tert-butyl-3-methylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), 3,9-bis[2-[3-(3-tert-butyl-4-methylphenol)] [-hydroxy-5-methylphenyl]propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylidene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], phenylpropionic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy,C7-C9 Side-chain alkyl esters, 2,4-dimethyl-6-(1-methylpentadecanyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3”,5,5',5”-hexa-tert-butyl-a,a',a”-(trimethylmethyl-2,4,6-tolyl)tri-p-cresol, diethylbis[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]calcium phosphonate, 4,6-bis(octylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylenebis[3- (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-dimethylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, reaction products of N-phenylaniline and 2,4,6-trimethylpentene, phenols such as 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, picric acid, and citric acid;Tris(2,4-di-tert-butylphenyl) phosphite, tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxophosphazene-6-yl]oxy]ethyl]amine, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphorous acid, tetra(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphite, 6-[3-(3-tert-butylphenyl)] Phosphorus compounds such as butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxophosphoric acid cycloheptane; sulfur compounds such as dilaurate 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearate 3,3'-thiodipropionate, pentaerythritol tetra(3-lauryl thiopropionate), and 2-mercaptobenzimidazole; thioether compounds; amine compounds such as phenothiazines; lactone compounds; and vitamin E compounds. These can be used alone or in combination of two or more. From the viewpoint of improving storage stability and heat resistance, compounds containing amine antioxidants and / or thioether compounds are preferred, and compounds containing thioether compounds are more preferred. The amount of component (G) (antioxidant) relative to 100 parts by weight of component (A) is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 4 parts by weight, further preferably 0.05 to 3 parts by weight, particularly preferably 0.1 to 3 parts by weight, and most preferably 0.5 to 3 parts by weight. By using 0.01 to 5 parts by weight, there is no risk of reducing bond strength or cohesive failure rate.

[0060] [(H) component]

[0061] In the moisture-curing resin composition described in this method, a colorant may also be added as a (H) component. Examples of (H) components include inorganic pigments such as carbon black, barium sulfate, alumina white, clay, and titanium dioxide; organic pigments such as danshenone blue, quinacridone red, dioxazine violet, and phthalocyanine blue; and pigments such as ZnS:Ag, ZnS:Cu, ZnS:Mn, SrAl2O4:Eu, and Sr4Al. 14 O 25Fluorescent inorganic pigments, fluorescent organic pigments, and dyes such as Eu, Y₂O₂S:Eu, and Y₂O₃:Eu can be used individually or in combination of two or more. From the viewpoint of not reducing bond strength and cohesive failure rate, inorganic pigments are preferred, and carbon black is most preferred. The amount of component (H) (colorant) relative to 100% by mass of the moisture-curing resin composition is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, further preferably 0.1 to 3% by mass, particularly preferably 0.2 to 3 parts by mass, and most preferably 0.3 to 2% by mass. By keeping the amount of component (H) within the above range, there is no risk of reducing bond strength and cohesive failure rate.

[0062] [(I)INGREDIENTS]

[0063] In the moisture-curing resin composition described herein, an organic filler may be included as component (I). The organic filler can be any powder of an organic material composed of rubber, elastomer, plastic, polymer (or copolymer), etc. It can be used alone or in combination of two or more. Alternatively, a core-shell type or other multilayer organic filler may be used. The average particle size of the organic filler is preferably in the range of 0.05 to 50 μm. The amount of component (I) (colorant) relative to 100 parts by weight of component (A) is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 4 parts by weight, further preferably 0.05 to 3 parts by weight, particularly preferably 0.1 to 3 parts by weight, and most preferably 0.5 to 3 parts by weight. By keeping the amount of component (I) within the above range, there is no risk of reducing the bond strength and cohesive failure rate.

[0064] <Applications>

[0065] The moisture-curing resin composition described herein can be formulated as a single-component or a two-component form as needed. Furthermore, the moisture-curing resin composition described herein is best suited for use as an adhesive and sealant, but can also be used as an adhesive, coating agent, potting compound, etc., as required. The moisture-curing resin composition described herein can be used in various electrical / electronic, building, automotive, and civil engineering applications, but because it does not contain cyclic low-molecular-weight siloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane, it is particularly suitable for use in electrical / electronic components and automotive electrical components.

[0066] <Object to be adhered>

[0067] The moisture-curing resin composition described herein exhibits excellent bonding strength and stability to metals and plastics, making it suitable for bonding various materials, including dissimilar materials. There are no particular limitations on the metals used; examples include iron, aluminum, magnesium, copper, stainless steel, and titanium. Similarly, there are no particular limitations on the plastics used; examples include fiber-reinforced plastics (FRP), carbon fiber-reinforced plastics (CFRP), polyacrylic acid, polyester, polyamide, acrylonitrile-butadiene-styrene, 6,6-nylon, polycarbonate, polyacetal, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polyphenylene ether, polyetheretherketone, polyethylene, and polypropylene. There are no particular limitations on the rubbers used; examples include nitrile rubber, polyurethane rubber, silicone rubber, and ethylene propylene diene monomer (EPDM). Bonding of at least two of these materials to each other is possible. The surfaces of these materials can be pre-treated or left untreated. This method is suitable for bonding metals and plastics. In one embodiment, using the moisture-curing resin composition described herein, the bonding of metals (e.g., aluminum) and plastics (e.g., 6,6-nylon or polybutylene terephthalate) is performed with a shear bond strength of 0.7 MPa or more (preferably 0.8 MPa or more) calculated according to the method of the embodiments described later.

[0068] <Coating Method>

[0069] As a method for applying the moisture-curing resin composition described herein to the substrate, known methods for applying sealants and adhesives can be used. For example, methods utilizing an automatic coating machine such as dispensing, spraying, inkjet printing, screen printing, gravure printing, dipping, spin coating, etc., can be used. It should be noted that, from the viewpoint of coatability, the moisture-curing resin composition described herein is liquid at 25°C. The viscosity is preferably 1000 Pa·s or less at 25°C.

[0070] <Curing Method>

[0071] The curing temperature of the moisture-curing resin composition described in this method is not particularly limited, but is preferably 10°C to 50°C, more preferably 15°C to 30°C. Furthermore, the relative humidity is preferably 40%RH or higher, and the curing time is preferably 1 hour or more and less than 2 weeks (336 hours), more preferably 1 hour or more and less than 288 hours, more preferably 2 hours or more and less than 240 hours, particularly preferably 3 hours or more and less than 216 hours, and most preferably 5 hours or more and less than 192 hours. According to one embodiment, the moisture-curing resin composition described in this method is cured (aged) at 10°C to 50°C (preferably 15°C to 30°C) for 1 hour or more and less than 336 hours (preferably 2 hours or more and less than 288 hours, more preferably 2 hours or more and 240 hours, and more preferably 3 hours or more and less than 216 hours).

[0072] <Sealing Method>

[0073] There are no particular limitations on the sealing method using the moisture-curing resin composition described herein, and representative examples include FIPG (In-situ Molded Gasket), CIPG (In-situ Cured Gasket), MIPG (In-mold Molded Gasket), liquid injection molding, etc.

[0074] Example

[0075] The present invention will now be described in more detail by way of examples, but the present invention is not limited to these examples.

[0076] [Examples 1-3, Comparative Examples 1-6]

[0077] To prepare a moisture-curing resin composition, the following components are prepared.

[0078] <(A) Ingredients: Polyoxyethylene polymers with hydrolyzable silanes and (meth)acrylic polymers with hydrolyzable silanes>

[0079] (A-1) Composition: (a1) a polyoxypropylene polymer (polyepoxypropylene) with hydrolyzable silyl groups (trimethoxysilyl) at both ends and (a2) a (meth)acrylic polymer with two or more hydrolyzable silyl groups (dimethoxysilyl or / and trimethoxysilyl) on the side chain; trade name: MA451 (KANEKA CORPORATION); viscosity (23°C): 90 Pa·s (of (A-1) composition, (a1) is more than 50% by mass and (a2) is less than 50% by mass).

[0080] (A'-1) Composition: Polyoxyalkylene polymer with trimethoxysilyl groups at both ends; Trade name: SAX575 (KANEKA CORPORATION); Viscosity (23℃): 50 Pa·s

[0081] (A'-2) Composition: (meth)acrylic polymer with two dimethoxysilyl groups in the side chain; Trade name: SA100S (KANEKA CORPORATION); Viscosity (23℃): 210 Pa·s

[0082] <(B) Component: A silane coupling agent having one or more epoxy groups per molecule>

[0083] (B-1) Ingredients: 3-Epoxypropoxypropyltrimethoxysilane, Trade Name: KBM-403 (Shin-Etsu Chemical Co., Ltd.)

[0084] (B-2) Ingredients: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, trade name: KBM-303 (Shin-Etsu Chemical Co., Ltd.)

[0085] (B-3) Ingredients: 3-Epoxypropoxypropyltriethoxysilane, Trade Name: KBE-403 (Shin-Etsu Chemical Co., Ltd.)

[0086] (B'-1) Ingredients: N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, Trade name: KBM-603 (Shin-Etsu Chemical Co., Ltd.)

[0087] (B'-2) Ingredient: 3-Methacryloxypropyltrimethoxysilane, Trade Name: KBM-503 (Shin-Etsu Chemical Co., Ltd.)

[0088] <(C) Composition: Titanium Catalyst>

[0089] (C-1) Composition: Chelate-based titanium catalyst, diisopropyl bis(ethyl acetoacetate) titanate, trade name: TC-750 (Matsumoto Fine Chemical Co., Ltd.)

[0090] (C'-1) Ingredients: Zinc catalyst containing alkylamines; Trade name: K-KAT 670 (King Industries)

[0091] (C'-2) Ingredient: Dioctylbis[(1-oxododecyl)oxy]tin, Trade name: NEOSTANN U-810 (Nitto Chemicals Co., Ltd.)

[0092] <(D) Ingredient: Plasticizer>

[0093] (D-1) Ingredients: Castor oil modified fatty acid esters, Trade name: RIC-CIZER GR-301 (Ito Oil Co., Ltd.)

[0094] <(E) Composition: Inorganic filler>

[0095] (E-1) Composition: Untreated heavy calcium carbonate, Trade name: SOFTON 1800 (Bihoku Powdered Chemical Industry Co., Ltd.), Average particle size: 1.25 μm, Specific surface area: 18000 cm³ 2 / g

[0096] (E-2) Composition: Light calcium carbonate surface-treated with fatty acid soap; Trade name: KALFAIN 500 (Maruo Calcium Co., Ltd.); Average particle size: 0.05μm; Specific surface area: 5000cm³. 2 / g

[0097] <(F) Ingredients: Preservative Stabilizer>

[0098] (F-1) Ingredients: Methyltrimethoxysilane, Trade Name: KBM-13 (Shin-Etsu Chemical Co., Ltd.)

[0099] (F-2) Ingredients: Diphenyldimethoxysilane, Trade Name: KBM-202SS (Shin-Etsu Chemical Co., Ltd.)

[0100] <(G) Ingredient: Antioxidants>

[0101] (G-1) Ingredients: Thioether-based antioxidants; Trade name: ADK STAB AO-26

[0102] <(H) Ingredient: Colorant>

[0103] (H-1) Composition: Carbon black.

[0104] Weigh components (A), (B), and (D) through (H) in a stirred container and stir for 30 minutes. Then, add component (C) and stir for 1 hour. Detailed preparation quantities are shown in Table 1, with all values ​​expressed in parts by mass. Note that blank spaces in the table indicate that the component was not added.

[0105] For each moisture-curing resin composition obtained, the shear bond strength (AL / PA66) and shear bond strength (AL / PBT) were evaluated according to the following method. Furthermore, the cohesive failure rate was calculated in each shear bond strength determination.

[0106] [Shear bond strength (AL / PA66)]

[0107] A moisture-curing resin composition was applied to an aluminum (A1050P) test piece with a width of 25 mm, a length of 100 mm, and a thickness of 1 mm. Then, a 6,6-nylon test piece with a width of 25 mm, a length of 100 mm, and a thickness of 1 mm was attached and fixed to the aluminum (A1050P) test piece, with the overlapping surface being 25 mm × 10 mm × a gap of 1 mm. The test pieces were then cured at 23°C and 50% RH for 7 days. The shear bond strength (in MPa) was determined at 25°C using a universal tensile testing machine (tensile speed 50 mm / min) according to JIS K 6850:1999. The shear bond strength was set at the maximum strength value. The acceptance criterion for shear bond strength (AL / PA66) was set at ≥0.7 MPa.

[0108] [Shear bond strength (AL / PBT)]

[0109] A moisture-curing resin composition was applied to an aluminum (A1050P) test piece measuring 25 mm wide × 100 mm long × 1 mm thick. Then, a polybutylene terephthalate (PET) test piece measuring 25 mm wide × 100 mm long × 1 mm thick was attached and fixed to the aluminum (A1050P) test piece, with the overlapping surface measuring 25 mm × 10 mm × 1 mm gap. The test pieces were then cured at 23°C and 50% RH for 7 days. The shear bond strength (in MPa) was determined at 25°C using a universal tensile testing machine (tensile speed 50 mm / min) according to JIS K 6850:1999. The shear bond strength was set at the maximum strength value. The acceptance criterion for shear bond strength (AL / PBT) was set at ≥0.7 MPa.

[0110] [Cohesion Destruction Rate]

[0111] The failure state of the test specimens after the shear bond strength test is visually confirmed, and the area ratio of cohesive failure is calculated. Here, as the failure state, when observing the failure surface, the portions with residual cured material on both sides of the test specimen are judged as cohesive failure, and the portions without residual cured material on one side are judged as interface failure. The total area of ​​the observed failure surfaces is set to 100, and the area ratio of cohesive failure in the failure surfaces (total area) is calculated. The acceptable standard for cohesive failure rate is set to 100% (all failure surfaces are cohesive failure, and there is no interface failure).

[0112]

[0113] Examples 1-3 are moisture-curing resin compositions containing components (A) to (C). The test pieces composed of aluminum and 6,6-nylon, or aluminum and polybutylene terephthalate, exhibited excellent shear bond strength. Furthermore, the cohesive failure rate, an indicator of the stability of the adhesive properties, also showed no problems. On the other hand, Comparative Examples 1 and 2, which used component (B'), showed partial interfacial failure. Comparative Example 3, which used a tin catalyst as a curing catalyst, also showed low shear bond strength, with all components showing interfacial failure. Comparative Example 4, which used a zinc catalyst, also showed partial interfacial failure. Furthermore, it was confirmed that Comparative Example 5, which used only a polyoxyethylene polymer with hydrolyzable silyl groups instead of component (A), also showed low shear bond strength, with 100% interfacial failure. Comparative Example 6, which used only a (meth)acrylic polymer with hydrolyzable silyl groups instead of component (A), also showed low shear bond strength, with partial interfacial failure. As can be seen from the above, by containing components (A) to (C), it has high adhesive strength and stable adhesive performance.

[0114] Industrial applicability

[0115] This invention exhibits excellent bonding strength to metals and plastics, and thus possesses stable bonding performance. Therefore, it can be used as an adhesive and sealant in various fields involving different materials, making it extremely useful.

[0116] This application is based on Japanese Patent Application No. 2024-41819, filed on March 18, 2024, the disclosure of which is referenced and incorporated herein by reference in its entirety.

Claims

1. A moisture-curing resin composition comprising the following components (A) to (C): (A) Ingredients: Polyoxyethylene polymers with hydrolyzable silanes and (meth)acrylic polymers with hydrolyzable silanes; (B) Composition: A silane coupling agent having one or more epoxy groups per molecule; (C) Composition: Titanium catalyst.

2. The moisture-curing resin composition according to claim 1, wherein it does not contain a silane coupling agent having one or more amino groups in one molecule.

3. The moisture-curing resin composition according to claim 1 or 2, further comprising a plasticizer as component (D).

4. The moisture-curing resin composition according to claim 3, wherein, The component (D) is a castor oil-modified fatty acid ester.

5. The moisture-curing resin composition according to claim 1 or 2, further comprising an inorganic filler as component (E).

6. The moisture-curing resin composition according to claim 5, wherein, The (E) component comprises heavy calcium carbonate powder and / or light calcium carbonate powder.

7. The moisture-curing resin composition according to claim 3, wherein, The amount of component (D) is 1 to 100 parts by mass relative to 100 parts by mass of component (A).

8. The moisture-curing resin composition according to claim 1 or 2, further comprising a silane compound having no reactive functional group other than alkoxysilyl group in one molecule.

9. The moisture-curing resin composition according to claim 1 or 2, used for bonding plastic components.

10. A cured product obtained by curing the moisture-curing resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Polyether having molecular chain ends blocked by hydrolyzable silyl group and production thereof

    JP1988012632A

  • Copolymer having molecular chain terminal blocked with hydrolyzable silyl group and production thereof

    JP1988033425A

  • Polymer, manufacture and composition thereof

    JP2000154205A

  • Adhesive agent composition and adhesion process

    JP2006143985A

  • Synthetic DNA vectors and methods of use

    JP2024041819A